POLA KONSUMSI DAN KOMPONEN YANG DIPERTIMBANGKAN OLEH KONSUMEN TEH HITAM DAN TEH HIJAU DI KECAMATAN PURWOKERTO SELATAN - Auralia, Muthia; Sumanto, Bambang; Wijayanti, Irene Kartika Eka (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2023)
People consume black tea and green tea with certain characteristics in accordance with their wishes and needs. The rating of the product shows the attitude of the people towards a product as well and also reflects their preferences in spending and consuming a product. The aim of this research is to analyse the characteristics of black tea and green tea consumers, to analyse green tea and black tea consumption patterns, and to analyse the components that consideration the preferences of black tea and green tea consumers. Research was held in Southern Purwokerto Sub-district, started from February until March 2020. The number of samples for each black tea and green tea consumers are 50 respondents taken by using multistage random sampling. The analysis which is used is Descriptive Analysis and Factor Analysis. The results show that characteristics of black tea and green tea consumers are women in various range of age. Additionally, married consumers buy black tea and green tea to be consumed together with their family. Perspective of consumption patterns black tea and green tea once a day in the morning breakfast for black tea and in other activities for green tea. The consumption number for family is an average of 50g/months. There are three main components that form preferences on green tea, those are: personality from the tea, identity, and the image of the product. On the other hand, main components that form preferences on black tea are two, those are: image, and identity product.